Implementation of Pamali Cultural Values as Social and Cultural Resilience of the Panjalu Society in Ciamis Regency - Sanjaya, Sansan; Budiman, Agus; Sondarika, Wulan (Universitas Galuh, 2025)
Panjalu District in Ciamis Regency holds a strong tradition called pamali, an unwritten rule that binds the community’s life. Known for its rich culture, Panjalu still highly values pamali alongside other customs like the Nyangku Ritual Ceremony, preserved to prevent cultural loss. This research explores pamali from the community’s viewpoint and examines its role as social and cultural resilience. Using qualitative methods, including observation and interviews, the study finds that pamali is more than outdated prohibitions; it is a system of values upholding politeness, morality, social norms, order, and harmony with nature. Violating pamali evokes fear of negative consequences, making it effective in maintaining social order. Despite modernization pressures, pamali remains relevant and adaptable, helping Panjalu preserve cultural identity and social solidarity. Thus, pamali acts as a vital pillar for the community’s social and cultural resilience.